Legal Contracts and Legal Customs in the History of the Law of the Kazakh Society - ABDRASULOV, Ermek B.; GUBAIDULLIN, Murat G. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
The legal conditions created in Kazakh society through the Khansko-Biyskiycode before the colonization of Tsarist Russia were aimed at meeting the needs of community members and reflecting them in everyday life. Their diversity was limited after the accession of the Kazakh society to Russia. During the period of contractual relations between the Russian Empire and the Kazakh society, the main forms of contracts were introduced that arose in the practice of European countries. Analysis of the norms of customary law governing contractual relations in the Kazakh society was done. It was concluded that the content of contractual rights in the Kazakh society is structured and democratic. The legal system of Kazakh society before the period of accession to the Russian Empire was democratic in content, built on the basis of the principles of justice, equality, humanity, humanity. The vitality and nationality of Kazakh law manifested itself in the fact that even with the efforts of the tsarist government to colonize the region, it did not dare to completely destroy the traditional dispute resolution system in Kazakh society.